A pilot study assessing listening comprehension and reading comprehension in children with down syndrome: Construct validity from a multi-method perspective - Prahl, Alison; Schuele, C. Melanie (Frontiers in Psychology, 2022)
Obtaining valid assessments of language and literacy skills in children with Down syndrome (DS) presents a challenge as there is a paucity of information about the psychometrics of measures that are commonly used to measure listening and reading comprehension in this population. Evaluating the construct validity of measures that employ different methods is essential to ascertain the optimal method of assessment in individuals with DS and with typical developmental histories (TD). This pilot study aimed to evaluate the construct validity of four parallel measures of listening and reading comprehension. Participants included 19 individuals with DS (M = 17 years, 3 months; SD = 3 years, 6 months) and 19 word-level reading-matched children with TD (M = 7 years, 2 months; SD = 7 months). Participants completed norm-referenced assessments for four parallel measures of listening and reading comprehension. The four measurement methods were: (1) nonverbal response, (2) cloze procedure, (3) passage-level with close-ended questions, and (4) passage-level with open-ended questions. Participants completed additional assessments (e.g., cognition, language, speech) for descriptive purposes. Construct validity was assessed using the Multitrait-Multimethod Matrix (Campbell & Fisk, 1959), a correlation matrix arranged to facilitate the assessment and interpretation of construct validity of measures across various formats. For both study groups, we observed strong evidence of construct validity for three out of four measurement methods. Results using the multimethod perspective also indicated that the listening and reading comprehension constructs were not separable. The findings from this pilot study represent a first step toward determining optimal methods of listening and reading comprehension assessment for individuals with DS. Additionally, these results can inform outcome measure selection in future language and literacy research with children with DS.